A new species of Plagiodontes from Argentina, and new data on the anatomy of four other species in the genus (Gastropoda: Orthalicidae, Odontostominae) - Piza, Julia (2009)
Plagiodontes weyrauchi sp. nov. is among the smallest species in the genus Plagiodontes (Doering, 1877). Statistical multivariate analyses confirmed its distinctiveness from other species, mostly because of its high number of whorls (8-9.75), relatively small width, and low proportions of last whorl and aperture length to shell length; multivariate discriminant analysis applied to this species and its most similar relative, P. multiplicatus parvus, correctly identified 100% of specimens. Pallial and genital anatomy supports P. weyrauchi as a different species, mainly because of the position of the ureteric pore, the small general size of the genital system, the presence of an accessory lobe alongside the verge, and the vaginal internal structure. Internal anatomy of four other small-sized taxa in the genus was studied. Two of them have a verge with no accessory lobe [P. dentatus (Wood, 1828) and P. patagonicus (d'Orbigny, 1835)], while the remaining two have an accessory lobe with different characteristics [P. rocae Doering, 1881 and P. multiplicatus parvus (Hylton-Scott, 1952)]. Internal structure of the vagina also shows specific differences among Plagiodontes species; their phylogenetic significance will be further investigated.